PTPN22 Acts in a Cell Intrinsic Manner to Restrict the Proliferation and Differentiation of T Cells Following Antibody Lymphodepletion - Knipper, Johanna A.; Wright, David; Cope, Andrew P.; Malissen, Bernard; Zamoyska, Rose (Frontiers in Immunology, 2020)
Lymphopenic insult has been shown to precipitate the initiation of autoimmune disease in murine models such as the Non-obese diabetic mouse. Similarly, in man lymphopenia induced by mAb therapy, for instance Alemtuzumab as treatment for Multiple Sclerosis, can precipitate development of secondary autoimmune disease in up to 30 % of patients. We asked whether an identified autoimmune susceptibility locus might increase the risk of developing autoimmunity in the context of mAb-induced lymphopenia in a mouse model. A single nucleotide polymorphism (SNP) in the gene encoding the tyrosine phosphatase PTPN22 (R620W) is associated with multiple human autoimmune diseases, and PTPN22 has been shown to modulate T cell responses, particularly to weak antigens. In keeping with this, PTPN22-deficient or PTPN22 R619W mutant murine T cells adoptively transferred into immunodeficient lymphopenic hosts showed a higher lymphopenia-induced proliferation rate than WT cells. We induced lymphopenia by treating wild-type or PTPN22 knock-out mice with T cell depleting antibodies and monitored reconstitution of the T cell pool. We found that PTPN22 deficient T cells acquired a more activated effector phenotype, with significantly more IFNγ producing cells. This resulted from expansion driven by self-peptide MHC, as it was evident when the contribution of IL-7 to lymphopenic expansion was blocked with IL-7R Ab. Interestingly, Foxp3+ Tregs were also considerably expanded in PTPN22-deficient and PTPN22 R619W mice, as was the frequency of both CD25+ and CD25- CD4 T cells that produce IL-10. Using bone marrow chimeric mice, we showed that PTPN22 influenced development of both regulatory and effector T cell functions in a cell-intrinsic manner. Overall the expansion of Tregs is likely to keep the expanded T effector populations in check and sparing Treg during therapeutic mAb depletion may be a useful strategy to prevent occurrence of secondary autoimmunity.